PEMANFAATAN CERITA RAKYAT JAWA TENGAH SEBAGAI PENGUATAN PENDIDIKAN KARAKTER DALAM PEMBELAJARAN BAHASA INDONESIA - Dewi Aprilia Sari; Sumarwati Sumarwati; Purwadi Purwadi (Universitas Sebelas Maret, 2018)
The purpose of this study is to describe the use of Central Java folklore as a strengthening of character building on Indonesian learning. This research is a case study which belongs to qualitative research and uses document as the data analysis. The object of this research is Central Java folklore, classroom observation result, lesson plan and syllabus of VII grade second semester, and the interview script of teacher and student. The technique of subject taking used is purposive sampling. The technique of collecting data is observation, interview, and document analysis. The validity test is using method triangulation and source triangulation. The data analysis technique is interactive analysis technique which consists of data reduction, data display, and building meaning and interpretation.The researcher found that, first, the intrinsic element of Central Javafolklore was encouraged by the characters in each story. Second, the value of character building on Central Javafolklore that existed in the characters. Third, the use of Central Javafolklore in Indonesian learning begins with planning in the form of lesson plan development based on the syllabus that has been prepared by the government. The planning, the implementation of learning begins from preparing the physical and psychological learners by providing stimulus in the form of motivation.